2023
DOI: 10.1101/2023.02.13.528235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P-Selectin promotes SARS-CoV-2 interactions with platelets and the endothelium

Abstract: COVID-19 causes a clinical spectrum of acute and chronic illness and host / virus interactions are not completely understood. To identify host factors that can influence SARS-CoV-2 infection, we screened the human genome for genes that, when upregulated, alter the outcome of authentic SARS-CoV-2 infection. From this, we identify 34 new genes that can alter the course of infection, including the innate immune receptor P-selectin, which we show is a novel SARS-CoV-2 spike receptor. At the cellular level expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Biolayer interference (BLI) revealed that the SARS-CoV-2 S1 bound to recombinant human SELP immobilized on streptavidin (SA) biosensors in the presence of 75 mM NaCl at an average affinity of 15.17 nM (Figure B). Although the SARS-CoV S1 protein has been reported to have the ability to interact with SELP, we did not detect the association signals under the same experimental conditions using BLI (data not shown). To explore the functional relevance of SELP to viral infection, we evaluated the adherence of S1 to HUVECs in the presence and absence of SELP.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Biolayer interference (BLI) revealed that the SARS-CoV-2 S1 bound to recombinant human SELP immobilized on streptavidin (SA) biosensors in the presence of 75 mM NaCl at an average affinity of 15.17 nM (Figure B). Although the SARS-CoV S1 protein has been reported to have the ability to interact with SELP, we did not detect the association signals under the same experimental conditions using BLI (data not shown). To explore the functional relevance of SELP to viral infection, we evaluated the adherence of S1 to HUVECs in the presence and absence of SELP.…”
Section: Resultsmentioning
confidence: 64%
“…Although the S1-mediated viral attachment is a crucial process for SARS-CoV-2 infection, by which many antiviral agents, such as neutralization antibodies, peptide antagonists, , and decoy nanoparticles, have been developed for COVID-19 treatment, however, neither the S1 adherence nor the spike pseudovirion infection can accurately reflect the authentic viral infection. Fortunately, this shortcoming was remedied by a study carried out by Moreno et al, in which they found live SARS-CoV-2 employed SELP to bind to airway capillary beds . Since the S1 protein induced endothelial inflammation (Figure ) and platelet aggregation in a dose-dependent manner, and because anti-SELP treatment significantly decreased the SARS-CoV-2 loads in vivo , the enhancement effect of SELP on S1 attachment may contribute to the pathogenesis of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation